Der Plan Colombia: Anti-Drogendiskurse und US-Hegemonialpolitik in der Andenregion - Zelik, Raul (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 2001)
The Plan Colombia is legitimated with the war against drugs. But the USefforts in the region seem to have less to do with drug problems but with geostrategic aims: roll back of guerilla forces, stabilising a state in a geographic important region. The article highlights the historical roots of the conflicts in Colombia as well as the present situation.